Functional characterisation of Mss11p, a transcriptional regulator of pseudohyphal development, starch degradation and flocculation in Saccharomyces cerevisiae - Bester, Michael C. (Michael Christiaan) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2003.